Studies of Debenzylation, and Oxidative Cyclization of Certain N-Glucosylated-2,4-isodithiobiiuret with Thiocarbamide and Elemental Sulphur - Tayade, D.T. (Asian Journal of Chemistry, 2010)
Certain 1-aryl-2-S-benzyl-5-tetra-O-acetyl glucopyranosyl-2,4- isodithiobiurets, debenzylated with the help of thiocarbamide and elemental sulphur in presence of benzylamine and pyridine, respectively, have been investigated.